Blood Culture Contamination in the Clinical Microbiology Laboratory of a Teaching Hospital. (11th September 2019) - Xu, Kemin; Gilani, Sarwat; Wang, Hank; Fallon, John
Abstract: Objectives: Blood culture is one of the most important tests performed in clinical microbiology laboratories. However, blood culture contamination remains a problematic cause of diagnostic errors for laboratory diagnosis and patient management. This aim of this study was to determine blood culture contamination rates and tendency at Westchester Medical Center (WMC), a tertiary teaching hospital in suburban New York City. Methods: All blood culture tests at WMC received from January 2017 to December 2018, as well as some historical data from 2007 to 2014, were retrospectively retrieved. Blood culture contamination rates were determined according to the laboratory's predefined criteria. Results: From 2007 to 2014, a total of 209, 750 blood cultures were performed with an average contamination rate of 1.6% (ranging from 0.4% to 3.5% monthly). The total numbers of blood cultures performed in 2017 and 2018 were 27, 863 and 28, 047, respectively. The overall positive rate of blood culture was 6.8% in 2017 and 7.6% in 2018. The contamination rate of blood culture was 0.6% in 2017 and 0.9% in 2018 with very few variations among different months of the year, which was significantly lower than that of the national benchmark (~2.5%) on blood culture contamination. The majority of contaminants were Staphylococcus epidermidis, accounting for 87% of source contamination, followed by Corynebacterium species (5.5%), Bacillus species and Micrococcus species (3.5% each), and Propionibacterium species (0.5%). Conclusion: Adherence to current guideline on appropriate blood collection techniques and monthly monitoring and timely feedback to phlebotomists should be continued to keep a low contamination rate for blood culture, which is not only from the perspective of individual patient care but also from the standpoint of hospital epidemiology and public health.